Distribution Pattern of Tree Species and Richness along an Altitude Gradient in the Sub-Alpine Temperate Zone of Hindu Kush Mountainous Forests, Pakistan: Tree species richness along elevation gradient - Matiullah; Amjad ur Rahman; Zahid Ullah; Aamir Saleem; Rahmatullah Qureshi; David F.R.P. Burslem; Mashwani, Zia-ur-Rehman (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Lal-Koo Mountains Forest (LMF) is the most extensive vegetation type in the largest Hindukush Mountainous ranges of Pakistan, however highly overlooked compared to the Himalayan and Karakorum ranges. Here, we studied the conifer tree species regeneration, diversity, basal area, density, and species richness of the LalKoo Mountains Forest (LMF) along the altitude gradient. We used the quadrate (10 m × 10 m) sampling method for vegetation analysis at 54 different locations between 1970-3120 m elevations. We found a total of 115 species belonging to 58 families. We find the maximum value of Shannon’s -Winner index 3.603 at 2115 m and Simpson’s Diversity Index at 0.91 at 2290 m along an altitude gradient in lower elevation ranges. The current finding revealed that observed tree species richness shows a unimodal pattern with a peak at 2400 m in the mid–elevational range followed by a basal area peaked at 2300 m across the elevation gradient. We concluded that the high growth ratio of regenerates is due to open areas (free canopy space) likely available due to severe deforestation at low altitudes. In Lalkoo, tree density did not follow a regular trend, although the highest values were obtained around 2400 m and 2600 m along altitude. Our results also indicate that there is a narrow elevational range at high altitudes (near the timberline) measured from 2750 m – 3120 m, of the gradient. Furthermore, we discovered broader altitude ranges in the midst (relating well with the theory behind the mid-domain effect) in the range of 2345 m – 2750 m, but the lower altitude range assessed from 1970 - 2345 m does not reveal precise data for the reported species richness, which is a deviation from Stevens elevational Rapaport rule.